Recent Advances in Research on Inhibitory Effects of Seaweed Extracts Against Parasites - Wenbing Cheng; Xiangyang Yang; Dengfeng Yang; Ting Zhang; Liguang Tian; Jiahao Dao; Zheng Feng; Wei Hu (Marine Drugs)
Parasitic diseases pose a serious threat to the health of humans and the steady development of livestock husbandry. Although there are certain drug-based treatment methods, with the widespread application of drugs, various parasites are gradually developing drug resistance. Natural products are highly favored by researchers due to their characteristics such as low toxicity, multi-target effects, and low risk of drug resistance. The ocean, as the largest treasure trove of biological resources on Earth, has a special ecosystem (high pressure, high salt, and low oxygen). This enables marine organisms to develop a large number of unique structures during their survival competition. So far, a variety of compounds, such as terpenoids, have been isolated from the algae. As potential drugs, these compounds have certain curative effects on various diseases, including tumors, parasitic diseases, Alzheimer’s disease, and tuberculosis. This paper systematically reviews and analyzes the current advances in research on the antiparasite effects of seaweed extracts. The primary objective of this research is to formulate a conceptual foundation for marine pharmaceutical exploration, focusing on the creation of innovative marine-based medicinal compounds to overcome the emerging problem of parasite resistance to conventional treatments.